Understanding the implementation of coordinated specialty Care for Early Psychosis in New York state: A guide using the RE‐AIM framework. Issue 3 (22nd January 2019) - Mascayano, Franco; Nossel, Ilana; Bello, Iruma; Smith, Thomas; Ngo, Hong; Piscitelli, Sarah; Malinovsky, Igor; Susser, Ezra; Dixon, Lisa
Abstract : Aim: Consistent evidence shows that early interventions for individuals with psychosis lead to improvements in symptoms, social functioning and treatment satisfaction. These results, combined with the allocation of specific funds for early psychosis services, have contributed to the emergence and dissemination of coordinated specialty care for early psychosis in the United States. Despite the rapid growth of such services across the country over the last 5 years, implementation processes are not yet well understood. We employ the RE‐AIM (Reach, Effectiveness, Adoption, Implementation and Maintenance) framework to describe processes, achievements and challenges of an early psychosis program called OnTrackNY that has been implemented in New York State. Methods: OnTrackNY is a coordinated specialty care program that delivers early intervention services that include both medications and psychosocial interventions to youths experiencing a first episode of non‐affective psychosis. By drawing on outcome and care process data that are collected quarterly from all OnTrackNY sites, we describe the status of each RE‐AIM dimension regarding OnTrackNY implementation followed by an evaluation of both achievements and shortcomings. Results: In general terms, OnTrackNY has shown to be a scalable and sustainable model for addressing early psychosis, reaching and providing recovery‐oriented services to a large population in need. Conclusion: Despite its advancements, a series of limitations pose challenges to the implementation and maintenance of the model including, but not to, the lack of incentives for coordination of services, the fragmentation of child and adult services, and concerns about financial sustainability.